Graphene and graphene-analogue nanosheets produced by efficient water-assisted liquid exfoliation of layered materials. (August 2016) - Manna, Kausik; Hsieh, Cheng-Yu; Lo, Shen-Chuan; Li, Yan-Sheng; Huang, Huin-Ning; Chiang, Wei-Hung
Abstract: We report the efficient productions of single- and few-layered graphene and molybdenum disulphide (MoS2 ) nanosheets using a surfactant-free, water-assisted liquid-phase exfoliation (LPE) of graphite and MoS2 bulk powders in N-methylpyrrolidinone (NMP). Extensive absorption spectroscopic study and materials characterizations indicate that the addition of water to NMP was not only effective on the exfoliation yields but also the stability of the colloidal dispersions of exfoliated nanosheets in the water-NMP mixed solvent upto 18 months. Detailed micro Raman spectroscopic analysis suggests the defects of the exfoliated graphene nanosheets were reduced using the developed water-assisted LPE in NMP.